The islamic republic of Iran’s export of human rights violations through proxies: Yemen and the case of the Bahá’ís - Moinipour, Shabnam (Religion and human rights, 2022)
Following the 1979 Revolution, the new regime began propagating a pan-Islamic ideology in order to unify Muslims under the rule of one country, the Islamic Republic of Iran. While it succeeded in recruiting proxies for this purpose, it has yet to succeed in materializing pan-Islamism. Iran’s proxies, who are currently active in Syria, Iraq, Yemen, Lebanon, the Palestinian territories, Afghanistan, and Pakistan are not only assisting Iran to reach its strategic goal of becoming the dominant power in the Middle East, but they are also beginning to import Iran’s human rights policies. One emerging example is the case of the Bahá’ís. In recent years, the Houthis, who are Iran’s proxy in Yemen, have begun severely persecuting the Bahá’ís in that country. The Bahá’ís in Yemen make only 1 percent of the non-Muslim population but they are the most persecuted group there. What this article aims to tackle are the reasons why there is a divergence in Iran’s bilateral versus multilateral export of human rights violation policies and why the Bahá’ís are a target of the Houthis in the middle of a conflict when this proxy has been created to fight against Saudi Arabia.